Doing child and adolescent psychotherapy : - Bromfield, Richard (John Wiley & Sons, 2007)
This readable guide for therapists and therapists-in-training lays out the theoretical essence and practical essentials of doing child and adolescent psychotherapy from the referral call to the last goodbye.